Optimalisasi Pengelolaan Simrs pada Unit Nurse Station Rawat Jalan di Rumah Sakit Mata Pekanbaru Eye Center Tahun 2024 - Nurfarahin Nurfarahin; Aldiga Rienarti Abidin; Raja Rachmadhina (Syntax Corporation Indonesia, 2025)
This study aims to optimize the management of the Hospital Management Information System (SIMRS) in the nurse station unit of the outpatient department at Pekanbaru Eye Center Hospital. Observations revealed various technical and operational challenges, including limited IT staff, lack of user training, and inadequate SIMRS infrastructure and features. The research methodology involved a priority problem analysis using the USG method (Urgency, Seriousness, Growth) and Fish Bone Diagram to identify root causes. Proposed interventions include intensive training, development of relevant SIMRS features, technological infrastructure upgrades, standardized SOP preparation, and regular monitoring and evaluation. The findings suggest that these measures have the potential to significantly improve operational efficiency, data accuracy, and the quality of hospital services. The study’s implications are expected to assist hospitals in addressing digitalization challenges in the healthcare sector.